Preferred exercise and mental health of the patients with fibromyalgia syndrome - Steffens R.D.A.K. (2020)
© 2020Background and purpose: Preferred exercise may be beneficial for the mental health of patients with fibromyalgia syndrome (FMS).This study aimed to investigate the effects of preferred exercise on the quality of life (Qol), depression, and mood states of the patients with FMS. Materials and methods: This study was a nonrandomized controlled trial. The patients with FMS were divided into an experimental group (EG; n = 22) and a control group (CG; n = 14). The patients in the EG performed their preferred exercise (resistance, walking, or stretching) for 12 weeks. CG went to a waiting list. Fibromyalgia Impact Questionnaire, Beck Depression Inventory, and Brunel Mood Scale were used to evaluate the outcomes. Results: The EG exhibited a decrease in the total impact of FMS on the Qol, depression, tension, and mental confusion (p < 0.01). Conclusion: Preferred exercises reduced the impact of FMS on the Qol, depression, and mental confusion of patients with FMS.